Immunotherapy with STING and TLR9 agonists promotes synergistic therapeutic efficacy with suppressed cancer-associated fibroblasts in colon carcinoma - Hajiabadi, Sare; Alidadi, Soodeh; Montakhab Farahi, Zohreh; Ghahramani Seno, Mohammad M.; Farzin, Hamidreza; Haghparast, Alireza (Frontiers in Immunology, 2023)
Innate immune sensing of nucleic acids by effective immunoadjuvants is critical for increasing protective immune responses against cancer. Stimulator of interferon genes (STING) and toll-like receptor 9 (TLR9) agonists are considered promising candidates in several preclinical tumor models with clinical translation potential. However, the effects of such treatment on tumor stroma are currently unknown. Here we studied the immunotherapeutic effects of ADU-S100 as STING agonist and CpG ODN1826 as TLR9 agonist in a preclinical model of colon carcinoma. Tumor-bearing mice were treated intratumorally on days 10 and 16 post-tumor inoculation with ADU-S100 and CpG ODN1826. Cytokine profiles in tumor and spleen, tumor cell apoptosis, infiltration of immune cells, and cancer-associated fibroblasts (CAFs) in the tumor microenvironment (TME) were evaluated to address the immunological mechanisms after treatment. The profound antitumor activity of single and combination treatment with upregulation of pro-inflammatory cytokines expression in tumor and spleen and recruitment and infiltration of immune cells to the TME revealed the synergism of immunoadjuvants in the eradication of the colon carcinoma model. As a remarkable finding, significant downregulation of CAFs in TME pointed to suppressed tumorigenesis after immunoadjuvant therapy. Our results illustrate the potential of targeting the STING and TLR9 pathways as powerful immunoadjuvant in preclinical colon carcinoma with the prospect of harnessing these pathways for further therapeutic approaches.